Aplikasi Kasir Penjualan Berbasis Web Menggunakan PHP dan MySQL: Studi Kasus Rumah Yatim Dan Tahfidz Qur’an Madani - Fitriyani; Fadzar Rusghana (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Rumah Yatim dan Tahfidz Qur'an Madani is an educational institution that plays a role in the field of religion, besides that, Rumah Yatim dan Tahfidz Qur'an Madani is now pioneering a sales business, currently Rumah Yatim dan Tahfidz Qur'an Madani still uses a manual data management system. Where the cashier still calculates each sales result manually like a calculator in general,. To overcome these problems, the need for a sales cashier application at the Madani Qur'an Orphanage and Tahfidz is expected with this application can make it easier for cashiers to collect financial data properly so that existing reports can be stored safely and effectively. This research was conducted at the madani qur'an orphanage and tahfidz house which is located at Jln. Kiara Sari V. No. 22 kel. Margasari Kec. Buah Batu Kab. Bandung. the time and implementation of the research was carried out for three months, starting on February 28, 2023 to April 10, 2023. In this research the system development method used is the Waterfall method. As for this research, the authors obtained data directly from the chairman of the head of the institution directly. The tools in the development of planning and design of this research are using the Unified modeling language (UML). This cashier application is made using PHP and MySQL as the database. based on the research that has been done, the results of the design of the student data application can be concluded that: 1. With the sales cashier application at the madani Qur'an Orphanage and Tahfid House, it can make it easier for cashiers to manage sales reports easily. 2. Storage of sales data at the Madani Qur'an Orphanage and Tahfidz can be stored safely and efficiently. because the data that was previously in paper form will be stored in Softfile form so that it does not require a lot of storage.